2019
DOI: 10.15446/dyna.v86n208.69300
|View full text |Cite
|
Sign up to set email alerts
|

Curvas Intensidad-Duración-Frecuencia no estacionarias para la cuenca del río Medellín

Abstract: Las curvas Intensidad-Duración-Frecuencia (IDF) actuales suponen que la precipitación no varía significativamente con el tiempo, subestimando así sus eventos extremos, lo que aumenta el riesgo de inundaciones y de daños en la infraestructura, es por esto que se deben estudiar metodologías que permitan su estimación en condición de cambio climático, es decir, con un enfoque no estacionario, tal como en este estudio, en el que se estimaron curvas IDF estacionarias y no estacionarias para 9 estaciones pluviográfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The hydrological characterization was done using two groups of information: rainfall and level data from measurements in stations located within the basin and the IFD curves (stationary and non-stationary) of the area obtained by Grajales (7,8). The design rainfall estimation was done for return periods from 2 to 100 years.…”
Section: Hydrological Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrological characterization was done using two groups of information: rainfall and level data from measurements in stations located within the basin and the IFD curves (stationary and non-stationary) of the area obtained by Grajales (7,8). The design rainfall estimation was done for return periods from 2 to 100 years.…”
Section: Hydrological Characterizationmentioning
confidence: 99%
“…Due to the increase in the intensity and frequency of precipitation in the Aburrá Valley (Antioquia, Colombia) (7,8), the continuous anthropization of the basin, changes in land use, factors associated with climate change and the intensification of the effects of the ENSO phases (9, 10), the characterization and modeling of peak flows with stationary and non-stationary conditions are required by the government entities in the upper basin of the Medellín River. This study shows the peak flow modeling for different return periods and stationary and non-stationary conditions with different soil moisture conditions.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…The traditional parametric method for constructing IDF curves is based on a statistical analysis of annual maximum series [7,8]. The method consists of calculating annual maximum intensities for different durations (usually 15, 30, 60, 120, and 360 minutes), followed by the fitting of a probability distribution that usually corresponds to one from the GEV (Generalized Extreme Value) family [9,10]. This distribution is used to calculate intensities for selected return periods (usually 2, 5, 10, 25, 50, and 100 years) [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies described above have shown that sub-daily rainfall information is the basis for calculating IDF curves using a traditional approach [1,10,17]. However, the development of IDF curves continues to be a challenge in the whole world, especially in countries from the Global South that have limitations, if not lack of this type of information [48].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation